PODMIOT ZYSKUJĄCY TOŻSAMOŚĆ W DIALOGU. JĘZYKOWE ŹRÓDŁA INTEGRALNOŚCI - Dobrzyńska, Teresa (Colloquia Litteraria, 2025)
The article addresses the issue of disintegration of the person and loss of sense of identity, a phenomenon perceived as a significant trait of postmodern culture. The author points to the factors that confirm the subject’s integrity, which reside in the very use of language, disposition toward building coherent utterances and ability to interpret semantically loose texts (pieces of poetry in particular). She argues that an alternative to the vision of a solipsistic and disintegrated subject, with a disturbed sense of identity, is a subject shown in development or progress, one that consciously seeks to achieve an identity and looks for a meaning in artistic productions and cultural artifacts. The individual tends to reinforce his or her integrity and develop a sense of identity in dialogue, as s/he confronts his/her views with those of the others whilst determining his/her own attitude towards values.